Migraine and gastrointestinal disorders in middle and old age: A UK Biobank study - Nike Zoe Welander (Brain and Behavior, 2021)
Introduction Migraine is a prevalent condition causing a substantial level of disability worldwide. Despite this, the pathophysiological mechanisms are not fully understood. Migraine often co‐occurs with gastrointestinal disorders, but the direction of a potential causal link is unclear. The aim of this project was to investigate the associations between migraine and several gastrointestinal disorders in the same cohort in order to determine the relative strengths of these associations. Methods This cross‐sectional study examined whether migraine is associated with irritable bowel syndrome (IBS), peptic ulcers, Helicobacter pylori (HP) infections, celiac disease, Crohn's disease and ulcerative colitis. Baseline data covering 489,753 UK Biobank participants (migraine group: n = 14,180) were analyzed using Pearson's chi‐square tests and adjusted binary logistic regression models. Results Migraine was significantly associated with IBS (odds ratio [OR] 2.24, 95% confidence interval [CI] 2.08–2.40, p <.001) and peptic ulcers (OR 1.55, 95% CI 1.35–1.77, p <.001). Migraine was not associated with HP infection (OR 1.34, 95% CI 1.04–1.73, p = .024), celiac disease (OR 1.29, 95% CI 1.04–1.60, p = .023), Crohn's disease (OR 1.08, 95% CI 0.80–1.45, p = .617) or ulcerative colitis (OR 1.00, 95% CI 0.79–1.27, p = .979) after adjusting for multiple testing. Conclusions Migraine was associated with IBS and peptic ulcers in this large population‐based cohort. The associations with HP infection, celiac disease, Crohn's disease, and ulcerative colitis did not reach significance, suggesting a weaker link between migraine and autoimmune gastrointestinal conditions or HP infection.